Design and implementation of an adaptive backstepping controller for a magnetic levitation system - Adiguzel, Fatih; Dokumacilar, Ersin; Akbati, Onur; Turker, Turker (SAGE PUBLICATIONS LTD, 2018)
Dynamics of magnetic levitation systems contain high order nonlinearities and uncertainties on the physical parameters. Despite of these uncertainties and nonlinearities, the main purpose of this study is to drive the position tracking error of the ball to zero. In order to achieve this, an adaptive backstepping controller is designed. After deriving the error dynamics and designing the adaptive backstepping controller, adaptation rules are defined for the uncertain model parameters and the gravitational acceleration in the system model. Numerical simulations are performed for different working conditions to test the designed controller and the adaptation rules. In addition to this, the viability of the proposed controller is verified through experimental studies and satisfactory results are obtained.
Keywords: Adaptive backstepping; magnetic levitation; NONLINEAR CONTROL; FEEDBACK; TRACKING; Automation & Control Systems; Instruments & Instrumentation